Seasonal fluctuations in MDD-W and nutrient dense food group intakes of women's diets in rural Zambia and Malawi (P10-137-19) - Kennedy, G.; Ahern, Molly B. (Elsevier, 2019)
To study seasonal variation in minimum dietary diversity of women (MDD-W) and food group intake for women of reproductive age (WRA) living in rural Zambia and Malawi where the effect of seasonal agricultural production and seasonal food availability on dietary diversity is likely to be high. 200 WRA living in Chitipa District, Malawi (n = 100) and Luwingu District, Zambia (n = 100) provided informed consent and were enrolled in a panel study. Households with at least one woman between age 15–49 were randomly selected. A dietary diversity questionnaire was administered every-other month for six rounds, from September 2017 to July 2018. MDD-W was calculated as the proportion of women consuming five or more out of ten food groups. Percent of women consuming each food group by round was also calculated. Chi square was used to test the difference in MDD-W across rounds. There was significant seasonal difference in the percentage of women achieving MDD-W. Lowest and highest proportion of WRA meeting MDD-W was 18% and 79% in Malawi (P < 0.05) and 28% and 70% in Zambia (P < 0.05). MDD-W followed expected variation, peaking in the season of greatest food abundance and lowering during the "lean" season. The food groups grains and tubers, dark green leafy vegetables and other vegetables dominate women's diets. Small fish species are the most commonly consumed flesh food, although availability and consumption decrease seasonally due to cold weather and annual fish bans. Vitamin-A rich fruits and vegetables, other fruit, and nuts and seeds are highly seasonal. Dairy and eggs are rarely consumed. Significant seasonal fluctuations in the proportion of WRA achieving MDD-W exist. This has implications for project monitoring and evaluation. Periods of abundance and scarcity for nutritionally important food groups were demonstrated. Attention should be given to improved nutrition-sensitive processing, storage and access to nutrient dense food groups affected by seasonal fluctuations. Research was funded by the International Fund for Agricultural Development (IFAD) with project partners McGill University, WorldFish, Bioversity International, Self Help Africa, University of Zambia, SPRODETA and the LUANAR and by the CGIAR research program on Agriculture for Nutrition and Health.